1998
DOI: 10.1038/32937
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin-family receptors associate with small G proteins to activate phospholipase D

Abstract: G-protein-coupled receptors of the rhodopsin family transduce many important neural and endocrine signals. These receptors activate heterotrimeric G proteins and in many cases also cause activation of phospholipase D, an enzyme that can be controlled by the small G proteins ARF and RhoA. Here we show that the activation of phospholipase D that is induced by many, but not all, Ca2+-mobilizing G-protein-coupled receptors is sensitive to inhibitors of ARF and of RhoA. Receptors of this type were co-immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
185
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 26 publications
4
185
0
1
Order By: Relevance
“…There are many examples of association of the GPCRs, including MOP with other proteins, such as beta-arrestins, (Lefkowitz, 1998), GRKs (Pitcher et al, 1998) and small G proteins (Mitchell et al, 1998). Different laboratories, including ours, have reported interaction of MOP C-tail with different proteins, such as periplakin (Feng et al, 2003), Phospholipase D2 (Koch et al, 2003), mPKCI (Guang et al, 2004), HSP40 {Ancevska-Taneva, 2006 #5292)and Filamin A (Onoprishvili et al, 2003).…”
Section: Introductionmentioning
confidence: 85%
“…There are many examples of association of the GPCRs, including MOP with other proteins, such as beta-arrestins, (Lefkowitz, 1998), GRKs (Pitcher et al, 1998) and small G proteins (Mitchell et al, 1998). Different laboratories, including ours, have reported interaction of MOP C-tail with different proteins, such as periplakin (Feng et al, 2003), Phospholipase D2 (Koch et al, 2003), mPKCI (Guang et al, 2004), HSP40 {Ancevska-Taneva, 2006 #5292)and Filamin A (Onoprishvili et al, 2003).…”
Section: Introductionmentioning
confidence: 85%
“…Subsequently, the crystal structure of bovine rhodopsin revealed that these residues are capable of interacting through a water molecule [110] thus validating the GnRH receptor models. Interestingly, this exchange prevents the human GnRH receptor coupling to phospholipase D by the small G-proteins ARF and RhoA, implying receptor conformationdependent signaling selectivity [98].…”
Section: Gnrh Receptor Structure and Functionmentioning
confidence: 99%
“…The substitution of the Asn residue in the NPXXY motif in different GPCRs has been shown to affect the activation of adenylyl cyclase [19], phospholipase C [20], [21], phospholipase D [22], and internalization pathways [23 -24].…”
Section: Homology Of Fatty Acid Binding Receptors To Class a Gpcrs Amentioning
confidence: 99%